The significance of community pharmacies' services beyond Dispensing Separation (DS) / Mohd Shah Rezan Hamzah - Hamzah, Mohd Shah Rezan (Faculty of Pharmacy, 2024)
The debate on dispensing separation (DS) for community pharmacists in Malaysia has been ongoing for decades, giving rise to numerous arguments [1, 2]. Despite the benefits of DS, which include optimizing patient safety, reducing medication errors, and lowering medication costs [3], the implementation of this policy in our country remains unachievable, despite strong public support and evidence [4].